Poverty Alleviation Studies Through Woman Empowerment - Rusdianti, Endang; Purwantini, Sri; Wahdi, Nirsetyo (Universitas Semarang, 2018)
The community poverty condition shows that there are still many women who do not work and less maximum of the effort to increase the income of prosperous families program (UPPKS) in Semarang Regency, which is only 30% active. In this process, the integration of women in development, especially women from the weak economic group, those with low income needs to be encouraged through increasing the ability and skills to carry out productive economic activities, in order to expand employment opportunities and create businesses for themselves through business groups that then develop in the form of cooperation. The study was conducted using qualitative method that sought to explore the problems directly from the participants so that the factors that could foster the interest and motivation of women to become entrepreneurs were obtained, the hope for prosperity and the establishment of business groups related to poverty alleviation efforts through women empowerment. The research participants were women entrepreneurs who joined the group (UPPKS) and family planning field officers in Semarang Regency. Data collection techniques were carried out by conducting interviews, observation / surveillance and documentation. Data validity used triangulation technique. The results of the field research were recorded, interpreted, extracted, analyzed to form categories, patterns and then formed as a mini theory. The final results of this study are the creation of prosition and mini theory on women empowerment studies in relation to poverty alleviation through social entrepreneurship which is expected to be guidance for business.